2014
DOI: 10.1371/journal.pone.0094151
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Decreases Murine and Human Pancreatic Tumor Cell Growth, Nuclear Factor-κB Activation, and Inflammation-Related Gene Expression in an Insulin-like Growth Factor-1−Dependent Manner

Abstract: Calorie restriction (CR) prevents obesity and has potent anticancer effects that may be mediated through its ability to reduce serum growth and inflammatory factors, particularly insulin-like growth factor (IGF)-1 and protumorigenic cytokines. IGF-1 is a nutrient-responsive growth factor that activates the inflammatory regulator nuclear factor (NF)-κB, which is linked to many types of cancers, including pancreatic cancer. We hypothesized that CR would inhibit pancreatic tumor growth through modulation of IGF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 40 publications
4
58
0
Order By: Relevance
“…Chronic inflammation is known to affect the tumor microenvironment in which leukocytes may enter and secrete proinflammatory factors [40,41]. Previously, we reported that CGA reduces NO, pro-inflammatory cytokines and an important adhesion molecule (Ninj1) through NF-κB inhibition, resulting in anti-inflammation in LPS-stimulated RAW 264.7 cells [16,42].…”
Section: Discussionmentioning
confidence: 97%
“…Chronic inflammation is known to affect the tumor microenvironment in which leukocytes may enter and secrete proinflammatory factors [40,41]. Previously, we reported that CGA reduces NO, pro-inflammatory cytokines and an important adhesion molecule (Ninj1) through NF-κB inhibition, resulting in anti-inflammation in LPS-stimulated RAW 264.7 cells [16,42].…”
Section: Discussionmentioning
confidence: 97%
“…Mice on calorie restriction had decreased serum IGF-1 levels, decreased expression of the proinflammatory genes, such as S100a9, F4/80, and macrophage chemoattractant, Ccl2. The inhibitory effects of calorie restriction on pancreatic cancer growth were postulated to be due to reduced NFkB activation mediated through the IGF-1 signaling pathway (9). Therefore, the interplay among the HFD/obesity axis and altered metabolic activities, inflammation, and oncogenic Kras signaling promotes the development of chronic pancreatitis, PanIN lesions, and progression to invasive pancreatic cancer (Fig.…”
mentioning
confidence: 99%
“…Initially, this pathway was shown to be important in maintaining self-renewal through leukemia inhibitory factor (LIF)-activated signalling [ 109 ]. Consistent with this observation, it was later reported that activation of AKT which is a major downstream component of this pathway, had similar effects in maintaining the pluripotency of cells [ 110 ].…”
Section: Pancreasmentioning
confidence: 78%